2023
DOI: 10.1002/aro2.6
|View full text |Cite
|
Sign up to set email alerts
|

The advances of the Chinese Brucella suis strain 2 vaccine

Abstract: Brucellosis, a worldwide crucial zoonotic disease, poses global socioeconomic risks to the system by threatening human health and animal reproduction. In recent years, with the increase of animal husbandry, animal brucellosis has become a remarkable health issue in China. To prevent and control the spread of brucellosis, Brucella suis live strain S2 vaccine has been licensed as a multivalent vaccine against the three major zoonotic Brucella species, for example, Brucella melitensis (small ruminants), Brucella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…The significant decrease in bacterial colonies detected in spleen specimens of immunized mice with vaccine candidates indicated that all investigated formulations conferred a strong protection against the infection. In a similar study, immunization with B. suis vaccine strain S2 ensured 92.3% protection in goats [63]. Moreover, remarkable protective efficacies of subunit antigens derived from B.abortus were also demonstrated in mice.…”
Section: Assessment Of Antibody Response and Challange Assaymentioning
confidence: 75%
“…The significant decrease in bacterial colonies detected in spleen specimens of immunized mice with vaccine candidates indicated that all investigated formulations conferred a strong protection against the infection. In a similar study, immunization with B. suis vaccine strain S2 ensured 92.3% protection in goats [63]. Moreover, remarkable protective efficacies of subunit antigens derived from B.abortus were also demonstrated in mice.…”
Section: Assessment Of Antibody Response and Challange Assaymentioning
confidence: 75%